المتطلبات الحديثة ضمن التفعيل و التطوير لدور القيـادة الحكـوميـة الإدارية في المنظمـات - زوبيـر, د / دغمـان (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
تعد الإدارة العامة حتى الآن مصدرا رئيسيا وأحد حقول المعرفة لتزويد وتطوير أداء المنظمات الحكومية والخاصة نظرا لما لها من دور فعال في دعم جهود تحقيق تنمية إدارية واقتصادية  مستدامة لكونها احد الأهداف الرئيسية التي تسعى الحكومات إلى تحقيقها من جهة و من زاوية أخرى كونها تطرح تساؤل حول البرهنة على أسس مفهومية الأساليب الحديثة و التعرف على الإمكانيات القيادية الإدارية وكيفية توفير الظروف اللازمة لفعاليتها وتعميق مساهمتها أملا في تقدم المنطقة بصفة عامة والتميز في تقديم الخدمات بصفة خاصة ، لكل هذا نعتبر أنه بات من الضروري وبصورة مستعجلة إعطاء أولوية للتنمية الإدارية نحو أداء متميز في القطاع الحكومي فأصبح التوجه نحو إ يجاد قيادات إدارية ذات كفاءة مسألة تحتل مكان الصدارة . الكلمات المفتاحية : الإدارة العامة -  القطاع الحكومي  - تنمية إدارية واقتصادية - قيادات إدارية  -  أداء متميز  The public administration until now a major source of one knowledge to provide and improve the performance of government and private organizations fields because of its active role in supporting the efforts to achieve administrative and economic sustainable development for being one of the main objectives that governments seek to achieve on the one hand and from another angle being asked a question about Demonstrated on the conceptual foundations of modern methods and identify potential administrative leadership and how to provide the necessary conditions for their effectiveness and their contribution to the deepening of hope in the progress of the region in general and excellence in the provision of services in particular. All of this we consider that it is necessary and urgently give priority for Administrative Development distinctively performance in the government sector became oriented towards the creation of an efficient administrative leadership issue occupies  pride of place . Key words : Public  administration - Public sector - Development of economic and Administrative - Administrative Leaders-  Excellent Performance.